Challenges of Communicating Science: Perspectives From the Philippines - Navarro, Kamila (Archīum Ateneo, 2020)
Science communication research is dominated by Western countries. While their research provides insight into best practices, their findings cannot be generalized to developing countries. This study examined the science communication challenges encountered by scientists and science communicators from Manila, Philippines through an online survey and semi-structured, investigative interviews. Their answers revealed issues which have been echoed in other international studies. However, challenges of accessibility and local attitudes to science were magnified within the Philippine context. These results indicate the ubiquity of certain challenges in science communication and the need for country-specific science communication frameworks. Further research on the identified challenges is needed on a local and global scale.